PENGENDALIAN WAKTU DAN TENAGA KERJA DENGAN SOFTWARE PRIMAVERA P6 (Studi Kasus: Proyek Pemangunan Gudang di Kabupaten Tuban) - Nur Sa'adah (Universitas Negeri Surabaya, 2025)
A common problem in construction projects is the difficulty of completing projects on time. Furthermore, resource utilization is often inefficient. A solution to this problem is to use the resource leveling method. The resource leveling method aims to minimize the uneven use of labor throughout the project. The purpose of this study was to determine the differences in project schedules and human resource allocation before and after the implementation of labor equalization. Project data in the form of work items, the duration of each job, the relationship between work items, and the number of workers per job were analyzed using Primavera P6 software to obtain the ideal human resource allocation. The results showed an increase in working time of 9 days or 3.4%. In addition, there were also changes in the resources of craftsmen and workers in September with a decrease of 12.2% each. In October, there was an increase in the number of craftsmen by 23 people and workers by 33 people.